Stress level and interdialytic weight gain (IDWG) in hemodialysis patients - Agastiya, I Made Cahyadi; Rismawan, I Made (Universitas Aisyiyah Yogyakarta, 2024)
Stress has various impacts on hemodialysis patients. Stress in hemodialysis patients can cause physical symptoms (fatigue, muscle cramps, nausea, and vomiting), a decrease in quality of life, and non-compliance with self-management, one of which is compliance related to limiting fluid intake, thus adversely affecting on the patient's IDWG. IDWG is an important indicator for fluid monitoring in hemodialysis patients. Increasing IDWG that exceeds the tolerance limit can have a negative impact and can even cause mortality. This study aimed to determine the correlation between stress level and IDWG among hemodialysis patients. This study was conducted in the hemodialysis unit of RSD Mangusada, involving 95 respondents. This study was quantitative, with non-experimental research using a cross-sectional approach. Data collection was carried out with DASS questionnaires for stress and observation sheets for the IDWG. The data was analyzed using Pearson's Spearman Rank (α<0.05). Respondents with IDWG within tolerance limits were the majority unstressed, and none experienced severe stress or very severe stress. There is a positive and weak correlation between stress and IDWG among patients undergoing hemodialysis. The findings from this study may provide useful information in reviewing existing nursing care and standards of care provided in hemodialysis units, including the need to consider psychological assistance services in the care of hemodialysis patients. Qualitative research is needed to explore the in-depth experience of stress in hemodialysis patients and the factors associated with it.